Grid congestion cost-based probabilistic transmission planning methodology for systems with intermittent wind power - Reyes, Rommel E.
With the increasing levels of wind in the grid, transmission planning must be able to account its effects in the power system. Particularly, its intermittent nature, priority dispatch as well as the resulting congestions in the network must be considered. Thus, there is a need to develop a planning methodology for the transmission system with intermittent wind power that can balance the investment in transmission and the costs incurred due to congestion if no investments in transmission will be made. This study developed a congestion cost-based methodology for probabilistic transmission planning with intermittent wind by considering the scheduled operation of the power system in a competitive electricity market as well as its uncertainties such as generator and branch outages, load variations and wind power intermittence. The proposed method estimated the expected congestion cost by using Probabilistic Load Flow through Monte-Carlo Simulation with DC-Optimal Power Flow. The method was applied to the Visayas Grid which demonstrated that the stochastic effect of wind to transmission planning can be analyzed and found that it can change the risk of overloading and the expected congestion cost, thereby establishing the overall viability of a related transmission project.